Pengembangan Aplikasi Mobile untuk Penjualan Ikan Hias pada Toko Gudang Jaya Aquarium - David Precius Panggabean (Prosiding SISFOTEK, 2025)
Technological developments in the current digital era have encouraged various business sectors to shift to online platforms, including in the trade sector. Gudang Jaya Aquarium, as one such business, still relies on a conventional sales system. This research aims to develop a mobile-based sales application to facilitate the store in managing transactions and providing information about ornamental fish care to customers. Meanwhile, the system development method applies the Scrum approach, which allows for an iterative and flexible development process according to user needs. Data were collected through observation, interviews, and literature studies. By implementing a mobile-based sales system, Gudang Jaya Aquarium is expected to assist in transaction management and increase customer satisfaction through the convenience of more modern and integrated transactions.